BIO-ACCUMULATION OF HEAVY METALS IN FIVE FISH SPECIES IN THE LOWER NIGER RIVER AT ILLAH, DELTA STATE. - EKELEMU, J.K; OKORO, K.O. (Nigerian Journal of Fisheries, 2020)
The bio-accumulation of heavy metals in the muscles, gills, liver, and gonads of five fish species sampled from River Niger at Illah, were determined, using the atomic absorption spectrophotometer (AAS). Data collected were analyzed using the bio-accumulation Quotient, Transfer Factor, Analysis of Variance and LSD at 5% probability. Nine heavy metals namely Copper (Cu), Nickel (Ni), Cobalt (Co), Chromium (Cr), Lead (Pb), Cadmium (Cd), Iron (Fe), Zinc (Zn), and Manganese (Mn)) were detected. There was a significant difference (P < 0.05) in the concentrations amongst the different organs. The order of accumulation in the organs was: liver > gonads > gills > muscles, except for Zinc, which had the order liver > gills >gonads > muscles. Generally, the order of accumulation was Zn > Fe >Mn> Ni > Cu > Cr > Co >Pb> Cd. The most accumulated metal was iron, while the least was Cadmium. Accumulation in all the organs combined were significantly different (P < 0.05). The values recorded were higher than the WHO acceptable limits showing the river at Illah to be under stress, polluted, and fishes contaminated with heavy metals.